Reexamining Climate Change Debates: Scientific Disagreement or Scientific Certainty Argumentation Methods (SCAMs)?. (June 2013) - Freudenburg, William R.; Muselli, Violetta
Despite strong scientific consensus that global climate disruption is real and due in significant part to human activities, stories in the U.S. mass media often still present the opposite view, characterizing the issue as being "in dispute." Even today, the U.S. media devote significant attention to small numbers of denialists, who claim that scientific consensus assessments, such as those by the Intergovernmental Panel on Climate Change (IPCC), are "exaggerated" and "political." Such claims, however, are testable hypotheses—and just the opposite expectation is hypothesized in the small but growing literature on Scientific Certainty Argumentation Methods, or SCAMs. The work on SCAMs suggests that, rather than being a reflection of legitimate scientific disagreement, the intense criticisms of climate science may reflect a predictable pattern that grows out of "the politics of doubt": If enough doubt can be raised about the relevant scientific findings, regulation can be avoided or delayed for years or even decades. Ironically, though, while such a pattern can lead to a bias in scientific work, the likely bias is expected to be just the opposite of the one usually feared. The underlying reason has to do with the Asymmetry of Scientific Challenge, or ASC—so named because certain theories or findings, such as those indicating the significance of climate disruption, are subjected to systematically greater challenges than are those supporting opposing conclusions. As this article shows, available evidence provides significantly more support for SCAM and ASC perspectives than for the concerns that are commonly expressed in the U.S. mass media. These findings suggest that, if current scientific consensus is in error, it is likely because global climate disruption may be even worse than commonly expected to date.